2004
DOI: 10.1080/01650250444000009
|View full text |Cite
|
Sign up to set email alerts
|

Perception of individualism and collectivism in Dutch society: A developmental approach

Abstract: Within Triandis's (1994) theoretical framework, two studies are reported that deal with the developmental course for subjective perceptions of cultural dimensions in Dutch society (i.e., vertical and horizontal individualism and collectivism). While perceptions of society are always subjectively determined, the perceived dimensions that are prevalent in society do not necessarily have to parallel subjective evaluations of the self in terms of the same dimension. In the first study, 245 secondary school pupils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 19 publications
3
36
1
Order By: Relevance
“…On the practical side, studying both men and women would be too broad for the scope of this paper. On the theoretical side, contemporary Dutch society is often depicted in the literature as being in favor of autonomy, emancipation, and gender equality (Oppenheimer 2004). In contrast, in more patriarchal societies such as Turkey and Morocco, cultural norms regarding the timing and sequencing of important family transitions are found to be stricter for women than for men (Bowen and Early 1993;Koc 2007).…”
Section: And Antillean Origin and Native Dutch Young Adults? (2) How mentioning
confidence: 99%
“…On the practical side, studying both men and women would be too broad for the scope of this paper. On the theoretical side, contemporary Dutch society is often depicted in the literature as being in favor of autonomy, emancipation, and gender equality (Oppenheimer 2004). In contrast, in more patriarchal societies such as Turkey and Morocco, cultural norms regarding the timing and sequencing of important family transitions are found to be stricter for women than for men (Bowen and Early 1993;Koc 2007).…”
Section: And Antillean Origin and Native Dutch Young Adults? (2) How mentioning
confidence: 99%
“…Specifically, U.S. culture is characterized as vertical-individualist, with emphasis on individual achievement (Triandis, 1995;Schwartz & Bardi, 2001) and Dutch culture as horizontal-individualist (Oppenheimer, 2004), with more emphasis on equality than achievement. These themes cohere with the GLOBE study's finding of a much stronger preference for performance orientation in the United States than the Netherlands (House et al, 2004).…”
Section: Study 2: Prescriptive Stereotypes About the Importance Of Lementioning
confidence: 99%
“…In contrast, Triandis (1996) defines horizontal collectivism as the inclusion of benevolent ideologies to collectivistic tendencies and vertical collectivism represents the addition of power to collectivism (Triandis, 1996). More specifically, Oppenheimer (2004) suggests that horizontal collectivists identify the self as a function of their in-groups and stress equality amongst members. In contrast, vertical collectivists emphasize the authoritarian structure of their in-group, often to the point of self-sacrifice and competition with out-groups (Oppenheimer, 2004;Triandis, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research examining the reliability and validity of the ICS supports the use of this scale cross-culturally and across ages (e.g. Oppenheimer, 2004;Gouveia, Clemente, & Espinosa, 2003;Choiu, 2001). Across studies, the ICS has been found to possess moderate to strong internal consistency (Cronbach's alpha ranging from 0.63 to 0.89) (Anthony, Rosselli, & Caparyan, 2003;Choiu, 2001;Gouveia, Clemente, & Espinosa, 2003;Oppenheimer, 2004;Singelis et al, 1995;Triandis & Gelfand, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation